(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In 2019, Ahsan et al. developed the concept of fuzzy \((m, n)\)-ideals in semigroups. Later, in 2022 Tiprachot studied \(n\)-interior ideals in ordered semigroups, which is a generalization of fuzzy ideals and interior ideals in semigroups. The aim of this paper is to study the concept of fuzzy \((m, n)\)-ideals and \(n\)-interior ideals in ordered semigroups and investigate the properties of fuzzy \((m, n)\)-ideals and \(n\)-interior ideals.